SPATIAL VARIABILITY OF SOIL PENETRATION RESISTANCE IN COFFEE GROWING - Andrade, Alan Delon; Faria, Rafael de Oliveira; Alonso, Diego José Carvalho; Ferraz, Gabriel Araújo e Silva; Herrera, Miguel Angel Diaz; Silva, Fábio Moreira da (Coffee Science - ISSN 1984-3909, 2018)
The intensive use of machines in agriculture tends to cause soil compaction, which can hamper the expansion of root system and the absorption of water and nutrients, thus affecting the crop development. In view of the above, the present study aimed to identify critical zones of soil compaction, through the spatial distribution of soil penetration resistance (SPR), having positions within the coffee rows and soil depth ranges as variables. The study was performed in a coffee plantation of 7.32 ha, belonging to the Bom Jardim Farm, located in the municipality of Bom Sucesso, MG, Brazil. The SPR was measured using a penetrometer in the depth range from 0 to 0.40 m, with discretization in four layers of 0.10 m. The data were interpreted based on geostatistics, in order to identify if there is spatial dependence of the SPR and generate thematic maps demonstrating the variable’s spatial behavior. It is concluded that there is spatial dependence of soil penetration resistance, being possible to use geostatistical tools to generate thematic maps based on classes of soil penetration resistance. The values of SPR in the tractor trail, for layers from 0.10 to 0.20 and from 0.20 to 0.30 m, were classified in the high SPR class and could cause damage to the crop.